Accounts of Culled Out Students from Board Programs: A Phenomenological Inquiry - Kristy Jane R. Muegna; Jonelson C. Escandallo; Deveyvon L. Espinosa (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2023)
The Culling System in every higher education institution ensures that only students who meet specific academic or performance standards remain in the program, which helps uphold the program's standards and effectiveness. Thus, this study aims to delve into the lived experiences of the students who were culled out from the board programs offered by the Kapalong College of Agriculture, Sciences and Technology in which qualitative research utilizing a phenomenological approach was utilized. The participants were the 14 students who were culled out from the board programs being offered by Kapalong College of Agriculture, Sciences and Technology who were purposively selected. Further, there were five (5) participants for the in-depth interview and another five (5) for the focus group discussion. The data gathered were analyzed through the use of coding and thematic analysis. The study is deemed beneficial since it can provide valuable insights into the effectiveness of culling practices in board programs wherein higher authorities can use this information to evaluate existing policies and programs related to student retention and support. It may lead to identifying potential flaws or areas for improvement in the current system.